Trend Estimation with Penalized Splines as Mixed Models for Series with Structural Breaks - Andreas Blöchl (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
On purpose to extract trend and cycle from a time series many competing techniques have been developed. The probably most prevalent is the Hodrick Prescott filter. However this filter suffers from diverse shortcomings, especially the subjective choice of its penalization parameter. To this point penalized splines within a mixed model framework offer the advantage of a data driven derivation of the penalization parameter. Nevertheless the Hodrick-Prescott filter as well as penalized splines fail to estimate trend and cycle when one deals with times series that contain structural breaks. This paper extends the technique of splines within a mixed model framework to account for break points in the data. It explains how penalized splines as mixed models can be used to avoid distortions caused by breaks and finally provides an empirical application to German data which exhibit structural breaks due to the reunification in 1990.
urn:nbn:de:bvb:19-epub-18446-2
Keywords: C22; C52; 330; penalized splines; mixed models; structural breaks; trends; flexible penalization